First COVID‐19 molecular docking with a chalcone‐based compound: synthesis, single‐crystal structure and Hirshfeld surface analysis study. Issue 12 (5th November 2020) - Alsafi, Mona A.; Hughes, David L.; Said, Musa A.
Abstract : The first investigation of a chalcone derivative as an inhibitor for COVID‐19 by a molecular docking study toward a possible drug for COVID‐19 is reported. Single‐crystal structure and Hirshfeld surface analyses confirmed the stacked packing in the chalcone. Abstract : The first example of molecular docking of the SARS‐CoV‐2 main protease for COVID‐19 [M pro, Protein Data Bank (PDB) code 7BQY ] by a chalcone‐based ligand, namely, ( E )‐1‐(2, 4‐dichlorophenyl)‐3‐[4‐(morpholin‐4‐yl)phenyl]prop‐2‐en‐1‐one, C19 H17 Cl2 NO2, I, is presented. Two‐dimensional (2D) LIGPLOT representations calculated for the inhibitor N3, viz. N ‐[(5‐methylisoxazol‐3‐yl)carbonyl]alanyl‐l ‐valyl‐ N 1 ‐((1 R, 2 Z )‐4‐(benzyloxy)‐4‐oxo‐1‐[(3 R )‐2‐oxopyrrolidin‐3‐yl]methylbut‐2‐enyl)‐l ‐leucinamide, and 7BQY are included for comparison with our chalcone‐based complexes. The binding affinity of our chalcone ligand with 7BQY is −7.0 kcal mol −1, a high value which was attributed to the presence of a hydrogen bond, together with many hydrophobic interactions between the drug and the active amino acid residues of the receptor. Docking studies were also performed, employing rigid and flexible binding modes for the ligand. The superposition of N3 and the chalcone docked into the binding pocket of 7BQY is also presented. The synthesis, single‐crystal structure, Hirshfeld surface analysis (HSA) and spectral characterization of heterocyclic chalcone‐based compound I, are also presented. The molecules are stacked, with normal π–π interactions, in the crystal.